Allergic reactions and their manifestations in dentistry: integrative review (Research, Society and Development, 2022)
Introduction: Allergy is a condition of hypersensitivity where the body responds excessively to an antigen. In dental practice, the most common are types I and IV. Type I reactions in the oral cavity manifest as angioedema, burning sensation or oral paresthesia, while in type IV hypersensitivity reactions, the symptoms are lichenoid reactions, erythema and stomatitis. The present study proposes to carry out an integrative review on the many causes of allergic reactions in the dental field and their interrelationships with other allergens, Methodology: searches were carried out in PubMed and LILACS databases using the terms “allergy”, “dentistry”, “ materials”, “allergic reaction” and “dentist” which were combined using the Boolean operators “AND”. Articles from 2002 to 2022 in English, Portuguese and Spanish were included and the search resulted in 21 articles. Results and Discussion: Dentistry has undergone great innovations and with that a range of materials are developed and made available on the market. Even created with biocompatibility principles, there are cases where failures in this principle are assumed, causing allergic reactions. These reactions are caused by several materials, the most common being latex gloves, anesthetics, impression materials and metals. Conclusion: Whenever there is a suspicion of allergy to some material, even if remote, the professional should change the care protocol using alternative materials to avoid medical emergencies in the dental office.